Penerapan Arsitektur Hijau pada Sequis Center Jakarta - Fitria Zubaidi; Diva Istiana Anggraeni; Sri Suryani Yuprapti W; Fairuz Muthia (Archvisual: Jurnal Arsitektur dan Perencanaan, 2023)
The topic of global environmental crisis comes up wherever and whenever, along with the worldwide environmental catastrophe in Indonesia, one of which is in Jakarta. This issue eventually led to the concept of green architecture to minimize new resources and save energy, creating a healthy and comfortable environment for its users. GBCI, an organization that evaluates whether a building fulfills the requirements for a green building using the Greenship grading system, is the foundation of the principles of implementing the concept of green architecture. Sequis Center, an office building in Senayan, South Jakarta's Sudirman Central Business District, is one of the buildings in Indonesia that achieved a gold grade in Greenship certification. Sequis Center uses the concept of environmentally friendly buildings through energy saving. This research uses a qualitative method by collecting data through literature studies, direct field observations, and analyzing the principles according to the concept of green architecture. Based on the conclusions of this research, the Sequis Center promotes sustainable environmental ecosystems by utilizing the green architecture concept. The results of this analysis can be added value to the building and are expected to increase knowledge about global warming that can be generated from buildings and activities in them.